Comparison of short and long forms of the Flinders program of chronic disease SELF-management for participants starting SGLT-2 inhibitors for congestive heart failure (SELFMAN-HF): protocol for a prospective, observational study - Iyngkaran, Pupalan; Hanna, Fahad; Andrew, Sharon; Horowitz, John David; Battersby, Malcolm; De Courten, Maximilian Pangratius (Frontiers in Medicine, 2023)
Introduction: Congestive heart failure (CHF) causes significant morbidity and mortality. It is epidemic and costs are escalating. CHF is a chronic disease whose trajectory includes stable phases, periods of decompensation and finally palliation. Health services and medical therapies must match the various patient needs. Chronic disease self-management (CDSM) programs that are patient focused, identify problems and set actionable goals appear as a logical, cost-friendly method to navigate patient journeys. Standardising and implementing programs for CHF have had setbacks. Methods and Analysis: SELFMAN-HF is a prospective, observational study to evaluate the feasibility and validity of the SCRinHF tool, a one-page self-management and readmission risk prediction tool for CHF; by comparing it with a proven, comprehensive CDSM tool. Eligible patients will have CHF with left ventricular ejection fraction <40% and commenced Sodium Glucose co-Transporter-2 Inhibitors (SGLT2-i) within 6 months of recruitment. The primary endpoint is the 80% concordance in readmission risk predicted by SCRinHF tool. The study will recruit >40 patients and is expected to last 18 months. Ethics and dissemination: This study has been approved by St Vincent’s ethics committees reference number: LRR 177/21. All participants will complete a written informed consent prior to enrolment in the study. The study results will be disseminated widely via local and international health conferences and peer reviewed publications.